IMPLEMENTASI DAN PENGEMBANGAN MASYARAKAT MELALUI PEMANFAATAN LIMBAH RUMAH TANGGA ORGANIK MENJADI PUPUK KOMPOS SEBAGAI SALAH SATU UPAYA DALAM MENCIPTAKAN DESA PROKLIM - Yanti Andriani, Neneng; Akmal, Muhammad; Chandra Permana, Septiahady; Dea Apriani, Kemala; Nurvianiar Sabri, Bertha; Subagja, Risko (JURNAL PENGABDIAN KEPADA MASYARAKAT (ADI DHARMA), 2023)
Trash accumulation can cause several problems, one of which is a polluted environment. Ignoring the accumulation of trash both intentionally and unintentionally will have a more severe impact on environmental damage. The results show that the accumulation of trash in Indonesia is increasing from year to year. Therefore, the role of the community in trash management is needed, one of which is in trash sorting. Trash that has been sorted can be used by category. This KKM activity aims to provide knowledge to the community about trash management, where trash that has been managed can be reused later. One of them is household trash (organic) into compost to improve food security as an application in the proklim program. The method used is a seminar related to the introduction of proklim, trash sorting, and processing household trash into compost. This trash processing activity is expected to take place in a sustainable manner because it will be able to reduce the accumulation of trash in Indonesia.